2018
DOI: 10.1097/md.0000000000010446
|View full text |Cite|
|
Sign up to set email alerts
|

CD133 expression correlates with clinicopathologic features and poor prognosis of colorectal cancer patients

Abstract: Background:CD133 has been identified as a putative cancer stem cell marker in colorectal cancer (CRC). However, the clinicopathological and prognostic significance of CD133 in CRC patients remains controversial. Thus, we conducted a meta-analysis to quantitatively evaluate the above issues.Methods:We collected a comprehensive literature search from PubMed, Web of Science, and Embase database up to September 20, 2016 examining CD133 and clinical features of colorectal cancer patients. We used the odds ratio (OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 42 publications
(23 reference statements)
3
28
0
Order By: Relevance
“…Problems and controversies still arise from (i) inconsistent semantics and terminology in the field, (ii) putative, functionally non-linked or poorly-defined surrogate markers despite their potential prognostic and predictive value - this applies to many CD surface markers, e.g. the transmembrane glycoprotein CD133 studied herein 53 , 54 , and (iii) splice variants and posttranslational modifications of proposed CSC surrogate markers that are often not sufficiently discriminated in preclinical and clinical studies such as CD44, our second marker of interest 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Problems and controversies still arise from (i) inconsistent semantics and terminology in the field, (ii) putative, functionally non-linked or poorly-defined surrogate markers despite their potential prognostic and predictive value - this applies to many CD surface markers, e.g. the transmembrane glycoprotein CD133 studied herein 53 , 54 , and (iii) splice variants and posttranslational modifications of proposed CSC surrogate markers that are often not sufficiently discriminated in preclinical and clinical studies such as CD44, our second marker of interest 55 .…”
Section: Discussionmentioning
confidence: 99%
“…One example indicating CSCs contribution to drug resistance is that when tumors were treated with conventional anti-cancer drugs such as cisplatin, small number of cancer cells survived and the proportion of cells showing the CSC properties significantly increased [38,39] . Another example is that patient prognosis is much worse when cancer cells in tumor strongly express CSC markers like CD133 [40][41][42][43][44] . Furthermore, CSCs isolated from clinical breast tumor samples were reported to show strong resistance to various chemotherapeutic drugs [42] .…”
Section: Therapy Resistance Of Cscsmentioning
confidence: 99%
“…As for the clinical status of CRC patients, Kashihara [19] demonstrated that high CD133 expression in CRC correlated with poor clinical outcomes. Huang's group [20] confirmed from existing 37 studies that CD133 would be served as a poor predictive indicator in CRC patients, due to CD133 overexpression positively associated with late T category, distant metastasis, lymphatic invasion, vascular invasion, as well as with lower 5-year Overall Survival/Disease-Free Survival (OS/DFS) rate and higher HR of OS/DFS in CRC patients. This finding was almost in line with the study by Wang's team [21] .…”
Section: Discussionmentioning
confidence: 92%